Cenários Logísticos para a Indústria de Óleo e Gás no Brasil - Reis, Letícia Mattos Tavares Valente dos (2006)
This study is about logistics` scenarios for the oil and gas industry in Brazil. It is based on the American (Global Business Network) and French (La Prospective) schools and aims to develop the scenarios from nowadays to 2015. At the end of the study there are two possible scenarios to the oil Industry and four to the natural gas, as it is still growing. They are: Continuity or Growth for Oil and National Integration, Regionalized Integration, Regionalized Integration with LNG consumption or Shrink of the Industry for natural gas. Chapter 1 introduces the reader to the subject and shows how the study will be developed. Chapter 2 is about the applied methodology. Chapter 3 shows the scenarios today. Chapter 4 gives emphasis to the variables and actors to be considered. Chapter 5 builds the scenarios and Chapter 6 is the conclusion.